The More, the Merrier? Multiple Myoglobin Genes in Fish Species, Especially in Gray Bichir (Polypterus senegalus) and Reedfish (Erpetoichthys calabaricus). (19th April 2021) - Helfenrath, Kathrin; Sauer, Markus; Kamga, Michelle; Wisniewsky, Michelle; Burmester, Thorsten; Fabrizius, Andrej
Abstract: The members of the globin superfamily are a classical model system to investigate gene evolution and their fates as well as the diversity of protein function. One of the best-known globins is myoglobin (Mb), which is mainly expressed in heart muscle and transports oxygen from the sarcolemma to the mitochondria. Most vertebrates harbor a single copy of the myoglobin gene, but some fish species have multiple myoglobin genes. Phylogenetic analyses indicate an independent emergence of multiple myoglobin genes, whereby the origin is mostly the last common ancestor of each order. By analyzing different transcriptome data sets, we found at least 15 multiple myoglobin genes in the polypterid gray bichir ( Polypterus senegalus ) and reedfish ( Erpetoichthys calabaricus ). In reedfish, the myoglobin genes are expressed in a broad range of tissues but show very different expression values. In contrast, the Mb genes of the gray bichir show a rather scattered expression pattern; only a few Mb genes were found expressed in the analyzed tissues. Both, gray bichir and reedfish possess lungs which enable them to inhabit shallow and swampy waters throughout tropical Africa with frequently fluctuating and low oxygen concentrations. The myoglobin repertoire probably reflects the molecular adaptation to these conditions. The sequence divergence, the substitution rate, and the different expression pattern of multiple myoglobin genes in gray bichir and reedfish imply different functions, probably through sub- and neofunctionalization during evolution.